Proceedings of the 7th International Conference on Industrial Engineering (ICIE 2021) Volume I - Radionov, Andrey A.; Gasiyarov, Vadim R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book highlights recent findings in industrial, manufacturing and mechanical engineering, and provides an overview of the state of the art in these fields, mainly in Russia and Eastern Europe. A broad range of topics and issues in modern engineering is discussed, including the dynamics of machines and working processes, friction, wear and lubrication in machines, surface transport and technological machines, manufacturing engineering of industrial facilities, materials engineering, metallurgy, control systems and their industrial applications, industrial mechatronics, automation and robotics. The book gathers selected papers presented at the 7th International Conference on Industrial Engineering (ICIE), held in Sochi, Russia, in May 2021. The authors are experts in various fields of engineering, and all papers have been carefully reviewed. Given its scope, the book will be of interest to a wide readership, including mechanical and production engineers, lecturers in engineering disciplines, and engineering graduates.
The effect of longitudinal diffusion on the operation parameters of the packed distillation column in emulsification mode -- Theoretical study of the force heterogeneity of airless tires made of elastic polyurethanes -- Heating system for rigid wedge valves -- Research of the modified tooth-belt drive for the machining center -- Modified belt transmission with enhanced technical characteristics -- Improvement of the timber supply flow at Syktyvkar Plywood Mill LLC by upgrading KKS-10 -- On the issue of designing cantilever shafts with joint consideration of strength, endurance and rigidity -- Features of the use of structural polymer-composite materials for the manufacture of complex-shaped parts in small-scale production -- Evaluation of the accuracy of gears made of polymer composite materials.
Keywords: Industrial engineering; Production engineering; Machinery; Control engineering; Robotics; Automation; Industrial and Production Engineering; Machinery and Machine Elements; Control, Robotics, Automation; Industrial engineering -- Congresses; Materials -- Congresses; Production engineering -- Congresses